Interval cancers as related to frequency of recall to assessment in the South Australian population-based breast screening program: An exploratory study. (August 2022) - Boyle, Terry; Reintals, Michelle; Holmes, Andy; Buckley, Elizabeth; Roder, David
Abstract: Australian accreditation standards specify upper limits for percentages of women recalled for further assessment following screening mammography. These limits have been unchanged since national screening commenced circa 1990, although screening target ages have changed, and technology from analogue to digital mammography. This study compared 2804 women with interval cancers diagnosed since national screening began (cases) with 14, 020 cancer-free controls (5 controls per case), randomly selected after matching by age, round, screen type and calendar year of screening episode, to determine the odds of interval cancer by differences in clinic recall to assessment percentages. Within low numbers of recalls that were within accepted accreditation ranges, results did not indicate more frequent recalls to assessment to be associated with fewer interval cancers in the analogue era. However, more frequent recalls were associated with reduced interval cancers for digital screens. These results are not conclusive, requiring confirmation in other screening environments, especially those with larger numbers of digital screens. If confirmed, frequency of recalls to assessment may need adjustment to get the best trade-offs in the digital era between reduced odds of interval cancers from more recalls and increases in financial and non-financial costs, including increased potential for overdiagnosis. Highlights: Recall to assessment standards have not changed in Australian breast screening. Age ranges have changed and technology from film to digital mammography. Odds of interval cancers were compared by recall to assessment frequency. Recall frequency was associated with odds of interval cancer for digital screens. The study is exploratory - results need confirmation, particularly digital results.